A literature review on thermodynamic sorption models of radionuclides with some selected granitic minerals - Holgersson, Stellan; Kumar, Pawan (Frontiers in Nuclear Engineering, 2023)
The literature for radionuclide sorption on four common granitic minerals have been surveyed. Mainly, such studies were modelling using Thermodynamic Sorption Models were investigated. Although the studies give a far from concerted results, they agree on the necessity to model radionuclide uptake by granitic minerals with a combination of ion exchange and surface complexation reactions. For the sheet-silicates biotite and chlorite alkaline and alkaline earth mainly bind by ion exchange but there is also a clear pH effect for this, which shows the importance of protons competing with metal cations for the exchange sites. For multivalent metal cations, surface complexation is the model of choice since the binding to mineral surfaces seems to be strongly dependent on pH and to be little affected by an increase in ion strength. Anion sorption seems to be taking place also by surface complexation, where the sorption mainly takes place at low pH. For the feldspar minerals K-feldspar and plagioclase the sorption is also modelled by the two reaction mechanisms ion exchange and surface complexation. Surface complexation seems to be especially prevalent for the M(III) and M(VI) state, while ion exchange probably dominates M (II) uptake. Although the literature on these minerals is sparse, the studies show that also these minerals have considerable sorption capacity and must be considered if sorption onto granite is to be modelled from single mineral data. What is usually missing from these studies are more systematic variations in pH, ion strength and temperature. Instead, there is a certain overemphasis on the establishment of sorption isotherms.